The Estimation of Geoid Profiles in the Northwest Atlantic from Simultaneous Satellite Altimetry and Airborne Expendable Bathythermograph Sections - Mitchell, Jim L.; Dastugue, Jan M.; Teague, William J.; Hallock, Zachariah R. (1990)
Published in Jnl. of Geophysical Research, v95 nc10 p17, 965-p17,977, 15 Oct 1990.